Selection of Optimized Mix of Generation Technologies for Hybrid Renewable Energy Power Plant in Sri Lanka - Ratneswaran, K.; Amalendran, J.; Kokulasingam, V.; Alex Angelito, R.; Wickramasinghe, A.; Fernando, S.; Vigneswaran, P.; Atputharajah, A.; Mithulananthan, N. (My University, 2010)
A renewable energy source based hybrid power plant has been proposed as an economical option for Eluvaithivu, an isolated Islet located close to the Jaffna peninsula in Sri Lanka. Eluvaithivu is a small islet with 130 houses[1]. Seventy houses are supplied electricity by a 28 kVA diesel generator owned by the Ceylon Electricity Board (CEB) and supply is given approximately 6½hours per day. The average monthly consumption of the islet is 3,100 kWh. Cost of electricity generation is about 50 Rs/kWh while the average tariff charged by CEB is about 5 Rs/kWh. Due to this reason there is considerable amount of financial loss. This financial loss prevents the complete electrification and round the clock supply to this islet. This paper presents a scenario for supplying electricity demand to Eluvaithivu Islet by using minigrid hybrid power system consisting of renewable sources, battery and diesel generators. Some topologies of hybrid power system are considered, simulations are performed and the results are presented in order to find out the most efficient and economic way for providing the power supply to this Islet. The research study proposes a wind-diesel hybrid power system as the most cost effective generation technology for this Islet. This will enable supplying electricity round the clock to this Islet and minimize the financial loss by about 60%. Renewable energy contribution will be approximately 70% of the total energy demand.